Dresses and Children: the Myth of Domestic Happiness in Varda’s Le Bonheur - Quaranta, Kaitlyn (Romance eReview, 2017)
In Mythologies, Barthes expands the notion of myth to include modern-day confusions of the historical with the natural. Agnès Varda’s 1965 film Le Bonheur also explores a modern myth: the myth of domestic happiness. The film details the daily life of a young French couple, François and Thérèse, and their two children. Thérèse appears as the ideal of youth and femininity, making dresses from home and raising the children while her husband goes to work. When François begins an affair with postal worker Émilie and tells Thérèse of this affair, she drowns inexplicably; soon, however, her post as homemaker is filled by Émilie, who all-too-easily replaces her. In portraying domestic happiness as contingent upon the constant toil of the wife, who, in Le Bonheur, is often paired with images of fertility, Varda demonstrates that such happiness is nothing but a veneer. Rebecca J. DeRoo further investigates the falsity of this happiness in her comparisons of the images in Le Bonheur with those found in contemporaneous women’s magazines; this identification with women’s magazines is also found in Barthes’s “Novels and Children,” where he challenges women’s roles. Le Bonheur also examines the negative impact of such stringent roles and thus emphasizes the problem of their acceptance.